2016
DOI: 10.1530/rep-15-0463
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of blood–testis barrier by actin binding proteins and protein kinases

Abstract: The blood-testis barrier (BTB) is an important ultrastructure in the testis since the onset of spermatogenesis coincides with the establishment of a functional barrier in rodents and humans. It is also noted that a delay in the assembly of a functional BTB following treatment of neonatal rats with drugs such as diethylstilbestrol or adjudin also delays the first wave of spermiation. While the BTB is one of the tightest blood-tissue barriers, it undergoes extensive remodeling, in particular at stage VIII of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 122 publications
(159 reference statements)
0
35
0
6
Order By: Relevance
“…As a dynamic cell, Sertoli cells show dynamic changes in their microtubule patterns as germ cells progress through the various spermatogenic stages (Vogl & Guttman, 2008). In this process, BTB undergoes periodical reconstruction to facilitate spermiogenesis and spermiation (Li & Cheng, 2016). Microtubules are components of the cytoskeleton, it is the fundamental unit of the spindle that is required for mitotic and meiotic cell division (Helmke, Heald, & Wilbur, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a dynamic cell, Sertoli cells show dynamic changes in their microtubule patterns as germ cells progress through the various spermatogenic stages (Vogl & Guttman, 2008). In this process, BTB undergoes periodical reconstruction to facilitate spermiogenesis and spermiation (Li & Cheng, 2016). Microtubules are components of the cytoskeleton, it is the fundamental unit of the spindle that is required for mitotic and meiotic cell division (Helmke, Heald, & Wilbur, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The MT- and actin-based cytoskeletons are two distinctive cytoskeletal networks, supported by different binding and regulatory proteins in the testis [5, 8, 9, 20]. However, these two cytoskeletal networks are intimately associated structurally and functionally to support spermatogenesis [9, 19].…”
Section: Mt-based Cytoskeletonmentioning
confidence: 99%
“…1c, d). This coordinated effort is necessary to support the timely transport of step 19 spermatids across the epithelium in stage VII–VIII tubules to prepare for their release at spermiation in stage VIII tubules [19, 20]. But they are also necessary to facilitate the timely remodeling of the BTB to support the transport of preleptotene spermatocytes across the immunological barrier at stage VIII of the epithelial cycle [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…In the testis, BTB undergoes remodeling at stage VIII of the epithelial cycle during which the ‘old’ BTB above the preleptotene spermatocytes connected in clones undergoes gradual degeneration, which coincides with the gradual assembly of a ‘new’ barrier behind these spermatocytes (for a review, see [45]). Studies have shown that these events require extensive endocytic vesicle-mediated trafficking so that integral membrane proteins and their associated adaptors from the ‘old’ BTB site can be rapidly endocytosed and recycled to assemble the ‘new’ BTB to avoid exhausting the available cell junction proteins in the Sertoli cell (for a review, see [46]).…”
Section: Pcp Proteins In the Testismentioning
confidence: 99%